Let x 1 < x 2 < x 3 be the three real roots of the equation 2 0 1 4 x 3 − 4 0 2 9 x 2 + 2 = 0 . Find x 2 ( x 1 + x 3 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good analysis of this problem, and of determining the intermediate value.
Note: You should check that the other 2 roots are indeed real valued (which is implicit in the problem).
an easier way to solve the last part would have been vietas: x 1 x 2 + x 2 x 3 = 0 − x 1 x 3 = 2 0 1 4 x 2 2 which would take no time. my method was by "oserving"(more of a wierd form of rrt). but your one is nice(+1)
Log in to reply
The concern here is to figure out which root is x 2 . I don't see how much easier your approach is for the very last line of calculation.
Log in to reply
Wolfram is showing other two roots are real. I don't know how to prove it any hint.
Log in to reply
Log in to reply
@Calvin Lin – That is something I know, I am very stupid.
Log in to reply
@Department 8 – Not stupid, just forgetful. Sometimes, when we're concentrating on the harder stuff, we forget the simple stuff. This is why it's important to be grounded in the basics.
We observe that 2 0 1 4 1 is a root of given polynomial
Now sum of roots taken two at a time is zero because coefficient of x is zero,i,e, x 1 x 2 + x 2 x 3 + x 3 x 1 = 0 and also product of roots = − 2 = x 1 x 2 x 3 which is negative
This means there is exactly one negative root and two positive roots.
Since the sum of roots = 2 0 1 4 4 0 2 9
This means that the positive root other than 2 0 1 4 1 is greater otherwise the sum of roots cannot be greater than 2 0 1 4 2
So x 2 = 2 0 1 4 1
Now x 1 x 2 + x 2 x 3 + x 3 x 1 = 0
⟹ x 2 ( x 1 + x 3 ) = − x 1 x 3 = x 2 − x 1 x 2 x 3 = 2 0 1 4 1 2 0 1 4 2 = 2
Problem Loading...
Note Loading...
Set Loading...
Let n = 2 0 1 4 , then the given equation can be rewritten as:
n x 3 − ( 1 + 2 n ) x 2 + 2 = n x 3 − x 2 − 2 n x 2 + 2 = x 2 ( n x − 1 ) − 2 ( n x 2 − 1 ) = 0 .
Note that n x 2 − 1 = ( n x + 1 ) ( n x − 1 ) . Now we an factor the last expression as ( n x − 1 ) ( x 2 − 2 ( n x + 1 ) ) = 0
This means that n 1 is a root, and the other two roots are the roots of x 2 − 2 n x − 2 . Note that the constant term of the quadratic is negative, so one of the two roots is positive and the other is negative. In addition, by Vieta's Formulas, the roots sum to 2 n , so the positive root must be greater than 2 n in order to produce this sum when added to a negative value. Since 0 < 2 0 1 4 1 < 2 2 0 1 4 is clearly true, x 2 = 2 0 1 4 1 and x 1 + x 3 = 2 2 0 1 4 . Multiplying these values together, we find that x 2 ( x 1 + x 3 ) = 2 .
Upvote if you liked